Regenerated cellulose membrane incorporating photocatalytic zinc oxide as a bifunctional membrane for decoloration of methylene blue. (23rd November 2021) - Azmi, Azima; Lau, Kam Sheng; Chin, Siew Xian; Zakaria, Sarani; Chia, Chin Hua
Abstract: In this paper, the development of regenerated cotton linter cellulose membranes embedded with ZnO nanoparticles was conducted using the dissolution‐regeneration process. The physical and chemical properties of composite membranes were characterized using X‐ray diffraction, field‐emission scanning electron microscopy, Fourier‐transform infrared spectroscopy, ultraviolet–visible spectroscopy, and thermogravimetric analysis. The characterizations revealed that the addition of ZnO nanoparticles changes the crystallinity, bond properties, thermal properties, and hydrophilicity of the regenerated cellulose membrane. These nanocomposite membranes demonstrated good capability in water absorption, with pore volumes ranging from 3.6 to 2.1 cm 3 /g. In the photocatalytic studies, the cellulose membranes incorporating ZnO particles (1.6 wt%) can remove up to 87.6% of MB in 100 min under UV irradiation and also maintained reusability (84%) after sixth cycles after 6 months. Taken together, this bifunctional cellulose/ZnO membrane is a promising material for solving the wastewater crisis.